Young Investors’ Instagram Usage Behavior and Investment Risk Appetite - Gesti Memarista; Angela Merici Adinda Puspita (Management Research and Behavior Journal, 2021)
Online Social Network Sites (SNSs) provides a lot of information to understanding young investor behavior. As the interest of financial practitioners, the young investor has their own risk tolerance. So, this study aims to predict the investment risk appetite through the social networking sites (SNSs) as one of huge informations exchange platforms by using young investors’ Instagram usage behavior. This research uses investment risk appetite and extroversion personality as the dependent variables. Moreover, number of followers on Instagram, time spent on Instagram, frequency of log on to Instagram, the use of Instagram for self-expression, and the use of Instagram for social connection as the independent variables. The researchers use 300 young stock investors through online questionnaire. The results study show that number of followers on Instagram and the use of Instagram for social connection significantly affect the extroversion personality, the extroversion personality significantly affect the investment risk appetite. Otherwise, time spent on Instagram, frequency of log on to Instagram, the use of Instagram for self-expression do not significantly affect the extroversion personality. This result obtains the probability of understanding the young investor’s risk appetite through their Instagram usage behavior, so the financial consultant can gather the information to understand their current social network activities.